Digital inclusive finance, rural revitalization and rural consumption - Wei Li; Lu Zhang; Mingyue Pu; Hui Wang (PLoS ONE, 2025)
With the rapid development of technology and the evolution of the global financial system, digital inclusive finance has become a new way to promote rural revitalization and rural residents’ consumption with the power of financial technology. This study explores the relationship between digitally inclusive finance, rural revitalization, and rural residents’ consumption. Based on the panel data of 30 provinces and cities in China from 2011 to 2021, this study empirically examines the impact of digitally inclusive finance on rural residents’ consumption and the mediating and threshold effects of rural revitalization. The results reveal that digitally inclusive finance is conducive to the enhancement of rural residents’ consumption, and rural revitalization acts as a mediator. Meanwhile, there is a nonlinear positive correlation between the impact of digitally inclusive finance and rural revitalization on rural residents’ consumption, in which there is a double-threshold effect of digitally inclusive finance and rural revitalization in the lagged period. Based on the above findings, we believe that while promoting digitally inclusive finance, it is important to promote rural revitalization strategy in a timely manner, improve rural infrastructure, and continuously stimulate the impact of digitally inclusive finance on rural residents’ consumption.